2001
DOI: 10.1038/sj.onc.1204915
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of cell transformation by papillomavirus E5 proteins

Abstract: The papillomavirus E5 proteins are short, hydrophobic transforming proteins. The transmembrane E5 protein encoded by bovine papillomavirus transforms cells by activating the platelet-derived growth factor b receptor tyrosine kinase in a ligand-independent fashion. The bovine papillomavirus E5 protein forms a stable complex with the receptor, thereby inducing receptor dimerization and activation, trans-phosphorylation, and recruitment of cellular signaling proteins to the receptor. The E5 proteins of the human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
117
1
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(123 citation statements)
references
References 74 publications
2
117
1
3
Order By: Relevance
“…Down-regulation of MHC-I takes place at multiple levels: the transcription of the gene is reduced, the MHC-I heavy chain peptide is degraded [9] and the MHC-I complex is sequestered in the GA cisternae and prevented from reaching the cell surface [81]. The molecular mechanism by which BPV-1 E5 induces cell transformation lies in its binding to, and activation of, the cellular receptor for the platelet-derived growth factor (PDGF ) [48]. The viral oncoprotein and the receptor form stable complexes, in which the two proteins are in opposite orientation and E5 interacts with the transmembrane and juxtamembrane domains of the PDGF-R [41,50,103,128].…”
Section: E5mentioning
confidence: 99%
“…Down-regulation of MHC-I takes place at multiple levels: the transcription of the gene is reduced, the MHC-I heavy chain peptide is degraded [9] and the MHC-I complex is sequestered in the GA cisternae and prevented from reaching the cell surface [81]. The molecular mechanism by which BPV-1 E5 induces cell transformation lies in its binding to, and activation of, the cellular receptor for the platelet-derived growth factor (PDGF ) [48]. The viral oncoprotein and the receptor form stable complexes, in which the two proteins are in opposite orientation and E5 interacts with the transmembrane and juxtamembrane domains of the PDGF-R [41,50,103,128].…”
Section: E5mentioning
confidence: 99%
“…E5 activates platelet-derived growth factor (PDGF) breceptor tyrosine kinase in a ligand-independent fashion. BPV-1 E5 proteins have been shown to bridge two molecules of transmembrane PDGF receptors, resulting in receptor dimerization, activation and recruitment of cell signalling and proliferative proteins (DiMaio & Mattoon, 2001). In addition, BPV-1 E5 binds to the 16 kDa transmembrane subunit of vacuolar H + -ATPase (Goldstein et al, 1991), impairing the acidification of the Golgi apparatus and other intracellular organelles.…”
Section: E4 and E5mentioning
confidence: 99%
“…Additionally, many studies have shown that the BPV-1 E5 protein transforms cells by binding to and activating the cellular b receptor for the platelet-derived growth factor (PDGF b) (Petti et al, 1991(Petti et al, , 1997Petti and DiMaio, 1992;DiMaio et al, 2000;DiMaio and Mattoon, 2001). Evidence suggests that receptor activation by the E5 protein is induced upon its dimerization (Lai et al, 1998).…”
Section: Introductionmentioning
confidence: 99%